Endovascular Management of Rupture in Acute Type B Aortic Dissections. Issue 6 (June 2015) - Faure, E.M.; Canaud, L.; Marty-Ané, C.; Becquemin, J.-P.; Alric, P.
Abstract : Objective: Reports of thoracic endovascular aortic repair (TEVAR) for complicated acute type B aortic dissection (ABAD) bring together a large range of clinical presentations. With a 30 day mortality of 50% when managed with open surgery, rupture is the most devastating complication of ABAD. This study investigated the outcome of TEVAR for ABAD complicated by rupture (r-ABAD) to assess the results of this particularly critical subgroup. Methods: A review of consecutive TEVAR for r-ABAD in two tertiary referral centers was performed using a prospectively maintained database. Results: Between 2000 and 2013, 24 patients (mean age 71 years; 14 males) underwent TEVAR for r-ABAD. Sixteen (67%) were in shock (Systolic blood pressure <80 mmHg) before surgery. Seven patients had coverage of the left subclavian artery, of whom four had partial arch debranching procedures via cervical access concomitant with TEVAR. Median length of aortic coverage was 150 mm, median proximal oversizing was 13.3% (range 6.2–33.3%). Technical success was achieved in 100%. There were four in hospital deaths (16%). Two patients (8%) had paraplegia, but neither stroke nor renal insufficiency requiring dialysis occurred. During a mean follow up of 28 months, there was one aortic dissection related death and eight patients (40% of the surviving patients) required re-intervention. All re-interventions were managed endovascularly. At last follow up CT scan, eight patients (40%) had complete remodeling of the aortic wall. Conclusion: With 16% in hospital mortality and 8% early major complications, this study confirms the feasibility of TEVAR for r-ABAD with a lower peri-operative morbidity and mortality rate compared with open surgery. Given the high rate of re-intervention, close follow up is required in surviving patients.